2020
DOI: 10.3390/su12177083
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Pro-Environmental Behaviour and Sustainable Development in Malaysia

Abstract: This study aimed to examine the role of environmental commitment, environmental consciousness, green lifestyle, and green self-efficacy in influencing pro-environmental behaviour. Data were obtained through a survey of 72 students at one of the training centers in Malaysia. The hypothesized relationships were tested using partial least squares (PLS) methodology. Results showed that environmental commitment, environmental consciousness, green lifestyle, and green self-efficacy positively influenced pro-environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 78 publications
(177 reference statements)
9
118
0
10
Order By: Relevance
“…It is still unclear how to create new value in the circular economy and from industries where sustainability plays a crucial role, for example, in the retail industry. The link between digital transformation and pro-environmental behaviors of customers, especially from a psychological perspective, appears as a pretty new and promising stream of research ( Yusliza et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is still unclear how to create new value in the circular economy and from industries where sustainability plays a crucial role, for example, in the retail industry. The link between digital transformation and pro-environmental behaviors of customers, especially from a psychological perspective, appears as a pretty new and promising stream of research ( Yusliza et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it may present some elements that characterise it, which can lead to more in‐depth studies to define a business model (Nielsen et al, 2018; Piccarozzi et al, 2018). Morrar, Arman, and Mousa (2017) identify a relationship between sustainability and IoT application with implications for the well‐being of the population (Yusliza et al, 2020). These authors highlight how the use of innovative technological tools, like hybrid cars, can contribute to pro‐environmental and sustainable behaviours.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results show that an environmental education curriculum should be well planned to deal passionately with the environment. Researchers have suggested that positive environmental consciousness shapes pro-environmental behaviour [163].…”
Section: Promoting Pro-environmental Behaviour Among Studentsmentioning
confidence: 99%